2019
DOI: 10.3390/molecules24091821
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Aerogel Fibers Made via In-Situ Gelation of Aramid Nanofibers with Polyamidoxime for Uranium Extraction

Abstract: The uranium reserve in seawater is enormous, but its concentration is extremely low and plenty of interfering ions exist; therefore, it is a great challenge to extract uranium from seawater with high efficiency and high selectivity. In this work, a symbiotic aerogel fiber (i.e., PAO@ANF) based on polyamidoxime (PAO) and aramid nanofiber (ANF) is designed and fabricated via in-situ gelation of ANF with PAO in dimethyl sulfoxide and subsequent freeze-drying of the corresponding fibrous gel precursor. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 53 publications
(75 reference statements)
1
39
0
Order By: Relevance
“…In particular, the number of BC nanofibers per unit volume was enhanced by secondary shaping, which further enhanced the adhesion of silica particles to the BC nanofibers. Based on the results of a BET test, the specific surface areas of the samples grew from 367.9 to 606.9 m 2 /g ( Table 1 ) with an increase in TEOS concentration, which is higher than that of PAO@ANF symbiotic aerogel fiber [ 28 ] and Kevlar aerogel fibers [ 25 ]. This is because a gel skeleton composed of inorganic oxide nanoparticles has a rougher surface compared to a gel skeleton composed of nanofibers or nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the number of BC nanofibers per unit volume was enhanced by secondary shaping, which further enhanced the adhesion of silica particles to the BC nanofibers. Based on the results of a BET test, the specific surface areas of the samples grew from 367.9 to 606.9 m 2 /g ( Table 1 ) with an increase in TEOS concentration, which is higher than that of PAO@ANF symbiotic aerogel fiber [ 28 ] and Kevlar aerogel fibers [ 25 ]. This is because a gel skeleton composed of inorganic oxide nanoparticles has a rougher surface compared to a gel skeleton composed of nanofibers or nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…The stress–strain curves of CAFs obtained from tensile tests showed that the breaking stress was in the range of 4.5–5.4 MPa. All the samples showed good tensile strength, which was much higher than that of native silica aerogel fibers, and it was comparable or even superior to those of CA/PAA-SF aerogel fibers [ 41 ] (3 MPa), SF/GO aerogel fibers [ 36 ] (3.2 MPa), and PAO@ANF aerogel fibers [ 28 ] (4.56 MPa). Moreover, the curves also showed that the elongation at break of the sample decreased from 6.8% to 1.1% with increasing precursor concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, acetone or a DMSO aqueous solution is used as the coagulation bath. Alternatively, as shown in Figure 12C, Li et al [ 80 ] selected a polyamidoxime (PAO)/DMSO solution as the coagulation bath to prepare a symbiotic PAO@ANF aerogel fiber by spinning an ANF/DMSO dispersion into a PAO coagulation bath and subsequently freeze drying it.…”
Section: Macroscopic Morphologies Of Advanced Anf‐based Materialsmentioning
confidence: 99%
“…For uranium extraction, the immobilization of specific chemical group on porous materials is the most promising method 9,10 . Plenty of porous materials have been utilized, such as mesoporous silica 11,12 , polymers 13,14 , carbon nanomaterials 15 , MOF 16 , and even MXene 17 . Much progress has been made on the improvement of performance of the SSG and uranium extraction.…”
Section: Introductionmentioning
confidence: 99%